A "See and Treat" approach for high grade squamous intraepithelial lesion on cervical cytology - Charoenkwan K. (2014)
Objective: To examine the final histologic findings as well as to correlate colposcopic and histologic findings in patients who had a high-grade squamous intraepithelial lesion (HGSIL) on the Pap smear and underwent colposcopy followed by LEEP on the "See and Treat" basis without intervening colposcopically directed biopsy. Material and Method: The medical records of patients with HGSIL on cytology who underwent LEEP without prior cervical biopsy at Chiang Mai University Hospital over a 5-month period were reviewed. The authors summarized the final LEEP histologic results and correlated colposcopic and histologic findings in these patients. Results: Of 55 patients who had a see-and-treat LEEP, 53 patients (96%) had a high-grade intraepithelial lesion or higher There were 11 patients (20%) who had invasive squamous cell carcinoma. Of 4 patients with a low-grade lesion on colposcopic examination, all had a high-grade lesion or higher on final histology. Forty-four patients (96%) with high-grade impression on colposcopy had high-grade or more severe lesion on the final histologic diagnosis. Conclusion: For patients with a high-grade lesion on the Pap smear, LEEP according to the "See and Treat" approach appeared to be a reasonable alternative to conventional colposcopically directed biopsy, especially in low resource settings.